THE APPLICATION OF NEW MEDIA IN BRAND COMMUNICATION: THE IMPACT OF BRAND'S VISUAL IMAGE ON CONSUMER PURCHASE INTENTIONS (Journal of Creative Industry and Sustainable Culture, 2023)
The objective of this paper is to investigate whether visual technologies can influence consumer brand purchase intentions by altering the forms of consumer association, attention, and emotion. The research employs traditional quantitative research methods and collected a total of 156 valid questionnaires from Chinese consumers. The study findings indicate that association, attention, and emotion all positively influence consumer purchase intent. These results suggest that brands can enhance their brand communication by investing in visual marketing, thereby winning higher purchase intent from consumers. It confirmed the impact of corporate visual brand communication based on new media forms on Chinese consumers' purchase intentions and established that association, attention, and emotion are the key influencing factors. It enriched the research on brand communication in China and provided a brand communication lean management approach.